2011
DOI: 10.1111/j.1600-0684.2011.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and number of parturitions on uterine and ovarian variables in owl monkeys

Abstract: The uterine volume (UV) was directly proportional to the number of parturitions, which was the most important factor in the uterine growth of adult females (P < 0.05). The body weight and age of the animals showed a high positive correlation with UV (r = 0.5354, r = 0.6489, P < 0.01), respectively. The volume of the ovaries grew in proportion to the age of the females (P < 0.05). Puberty was the period of greatest uterine and ovarian growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 15 publications
7
14
0
1
Order By: Relevance
“…The results related to uterine evaluation in this study are very similar to those reported in previous studies performed with ultrasound in A. azarai infulatus . The simplex non‐pregnant uterus was characterized by a globular fundic portion and a small cervix that protruded into the vaginal canal, which is similar to other New World primate species , but different from apes, which have the fundic portion described as flattened .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results related to uterine evaluation in this study are very similar to those reported in previous studies performed with ultrasound in A. azarai infulatus . The simplex non‐pregnant uterus was characterized by a globular fundic portion and a small cervix that protruded into the vaginal canal, which is similar to other New World primate species , but different from apes, which have the fundic portion described as flattened .…”
Section: Discussionsupporting
confidence: 87%
“…According to ultrasound data of Coutinho et al. , after the first pregnancy the uterus enlarges, probably as a result of hormonal events and their influence on uterine development on size and weight . This enlargement after first pregnancy does not allow us to observe further variations in the uterine biometry related to the estrous cycle.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A espécie Aotus azarai infulatus é comumente utilizada como modelo em pesquisas biomédicas no Centro Nacional de Primatas (CENP/SVS/MS) (MONTEIRO et al, 2009;COUTINHO et al, 2011;TAKESHITA et al, 2011;LINS et al, 2012;MAYOR et al, 2015) e a utilização da espécie no presente estudo foi baseada no registro prévio da susceptibilidade de infecção por isolado humano do genótipo 2 do HEV em macacos-da-noite da espécie A.…”
Section: Fascicularis)unclassified